Fifty most influential articles on anorectal malformations: A tribute through bibliometric ranking - Anjan Kumar Dhua; Vipan Kumar; Ashwani Kumar Mishra; Vishesh Jain; Devendra Yadav; Minu Bajpai; Sandeep Agarwala; Prabudh Goel (Wolters Kluwer Medknow Publications, 2022)
Background: With the global assimilation of "publish and perish" culture into institutional academics, there has been an exponential rise in the publication numbers. There are ~2500 PUBMED entries related to "anorectal malformation (ARM)." The young clinician in his pursuit to translate experimental research to bedside often finds himself lost "in the midst of plenty." This bibliometric analysis has been conducted to codify the seminal work on ARM for future reference and pay tribute to the most impactful articles. Materials and Methods: Thomson Reuters Web of Science citation indexing database and research platform was used to retrieve the most cited articles in ARM using appropriate search strings. The characteristics (name of authors, the total number of authors, the title of publication, journal of publication, year of publication, etc.,) of the 50 top-cited articles were analyzed. Results: The analysis revealed that the Journal of Paediatric Surgery was leading the choice of journal for publication. While most of the publications originated from the United States of America, Alberto Pena was the most influential author. The most studied topic was on associated malformations, and the most common study design was cohort studies. Conclusion: The approach of citation analysis provided us an opportunity to retrieve the most influential articles on ARM. The trends in research in ARM have also been analyzed, spreading over five decades.